2005
DOI: 10.1074/jbc.m413819200
|View full text |Cite
|
Sign up to set email alerts
|

O-GlcNAcase Uses Substrate-assisted Catalysis

Abstract: The post-translational modification of serine and threonine residues of nucleocytoplasmic proteins with 2-acetamido-2-deoxy-D-glucopyranose (GlcNAc) is a reversible process implicated in multiple cellular processes. The enzyme O-GlcNAcase catalyzes the cleavage of ␤-O-linked GlcNAc (O-GlcNAc) from modified proteins and is a member of the family 84 glycoside hydrolases. The family 20 ␤-hexosaminidases bear no apparent sequence similarity yet are functionally related to O-GlcNAcase because both enzymes cleave te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
311
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 340 publications
(333 citation statements)
references
References 65 publications
(66 reference statements)
18
311
1
Order By: Relevance
“…The value we observe most closely resembles that seen for GH84 human O-GlcNAcase ( ranging from Ϫ0.42 to Ϫ1.6 for GH84 enzymes) (15,19) but is significantly less that those observed for GH20 enzymes (* ranging from Ϫ1.0 to Ϫ1.29) (15, 37). The good correlation we observe here, coupled with the similarity of value to values observed for enzymes from GH84, provides strong kinetic evidence that these enzymes share in common a catalytic mechanism involving substrate assistance.…”
Section: Resultssupporting
confidence: 58%
See 2 more Smart Citations
“…The value we observe most closely resembles that seen for GH84 human O-GlcNAcase ( ranging from Ϫ0.42 to Ϫ1.6 for GH84 enzymes) (15,19) but is significantly less that those observed for GH20 enzymes (* ranging from Ϫ1.0 to Ϫ1.29) (15, 37). The good correlation we observe here, coupled with the similarity of value to values observed for enzymes from GH84, provides strong kinetic evidence that these enzymes share in common a catalytic mechanism involving substrate assistance.…”
Section: Resultssupporting
confidence: 58%
“…(Fig. 1D) is a potent inhibitor of glycoside hydrolases from GH20 (15,16) and GH84 (15) by virtue of its mimicry of the enzyme-catalyzed transition state (60) or the high energy oxazoline intermediate (Fig. 1B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although only a single gene exists for each enzyme, both are known to have several splice variants. O-GlcNAcase has two splice variants, a full-length version, whose localization is mainly cytosolic, and a catalytically less active nuclear-localized variant that is missing a putative histone acetyltransferase domain (16). For OGT, three variants have been identified, short-and full-length nuclear/ cytoplasmic localized versions and a mitochondrial localized enzyme (17).…”
Section: ␤-O-n-acetyl-d-glucosamine (O-mentioning
confidence: 99%
“…1) has been found to be a potent inhibitor of family 20 hexosaminidases 2, 3 and, more recently, family 84 O-GlcNAcases. 5 Its poor inhibitory potency toward family 3 is consistent with this family of enzymes. O-(2-Acetamido-2-deoxy-D-glucopyranosylidene)amino-Nphenylcarbamate (PUGNAc) 2, 12 the tetrahydroimidazopyridines, with the most important being 8-acetamido-5,6,7,8-tetrahydro-6,7-dihydroxy-5-(hydroxymethyl)imidazo[1,2-a]pyridine-2-acetic acid, gluco-nagstatin 3, 13 and the triazoles, all prepared by Vasella et al, have all been shown to potently inhibit family 3 b-N-acetylglucosaminidases, 14 family 20 human b-hexosaminidases 9, 13 and family 84 O-GlcNAcases.…”
Section: Introductionmentioning
confidence: 60%